Fatty acids are required for epidermal permeability barrier function. - Mao‐Qiang Man; Peter M. Elias; Feingold Kr (1993)
The permeability barrier is mediated by a mixture of ceramides, sterols, and free fatty acids arranged as extracellular lamellar bilayers in the stratum corneum. Whereas prior studies have shown that cholesterol and ceramides are required for normal barrier function, definitive evidence for the importance of nonessential fatty acids is not available. To determine whether epidermal fatty acid synthesis also is required for barrier homeostasis, we applied 5-(tetradecyloxy)-2-furancarboxylic acid (TOFA), an inhibitor of acetyl CoA carboxylase, after disruption of the barrier by acetone or tape stripping. TOFA inhibits epidermal fatty acid by approximately 50% and significantly delays barrier recovery. Moreover, coadministration of palmitate with TOFA normalizes barrier recovery, indicating that the delay is due to a deficiency in bulk fatty acids. Furthermore, TOFA treatment also delays the return of lipids to the stratum corneum and results in abnormalities in the structure of lamellar bodies, the organelle which delivers lipid to the stratum corneum. In addition, the organization of secreted lamellar body material into lamellar bilayers within the stratum corneum interstices is disrupted by TOFA treatment. Finally, these abnormalities in lamellar body and stratum corneum membrane structure are corrected by coapplication of palmitate with TOFA. These results demonstrate a requirement for bulk fatty acids in barrier homeostasis. Thus, inhibiting the epidermal synthesis of any of the three key lipids that form the extracellular, lipid-enriched membranes of the stratum corneum results in an impairment in barrier homeostasis.